Funding the New Biologics – CCOHTA Report on the Cost Effectiveness of Infliximab for Crohn’s Disease: Pearls and Pitfalls - John K Marshall (Canadian Journal of Gastroenterology)
The Canadian Coordinating Office for Health Technology Assessment (CCOHTA) published an economic analysis, using a Markov model, of infliximab therapy for Crohn’s disease that is refractory to other treatments. This was the first fully published economic analysis that addresses this treatment option. Health state transitions were based on data from Olmsted County, Minnesota, health state resource profiles were created using expert opinion and a number of assumptions were made when designing the model. The analysis was rigorous, the best available efficacy and safety data were used, state-of-the art sensitivity analyses were undertaken and an ‘acceptability curve‘ was constructed. The model found that infliximab was effective in increasing quality-adjusted life years when offered in a variety of protocols, but it was associated with high incremental cost utility ratios compared with usual care. The results should be interpreted, however, in view of a number of limitations. The time horizon for the analysis was short (one year), because of a lack of longer-term efficacy data, and might have led to an underestimation of the benefits from averting surgery. Because the analysis was performed from the perspective of a Canadian provincial ministry of health, only direct medical costs were considered. Patients with active Crohn’s disease are likely to incur significant indirect costs, which could be mitigated by this medication. The analysis should be updated as new data become available. Moreover, small changes in the cost of the medication could make the treatment cost effective, according to this model. Economic analyses, such as the one undertaken by the CCOHTA, cannot by themselves solve dilemmas in the allocation of limited health care resources, and other considerations must be included when formulating policy. This is especially important for patients with severe Crohn’s disease, who have significant disability and for whom few therapeutic options exist.